Optimalisasi Dosis Pupuk Kompos Untuk Meningkatkan Hasil Dan Kualitas Tanaman Kacang Panjang (Vigna Unguiculata L.) - Stefani Angel Kristin Hulu (CV. SINAR HOWUHOWU, 2025)
Yard-long bean (Vigna unguiculata L.) is an important horticultural commodity that requires optimal nutrition for maximum growth and production. This study aimed to determine the optimal dose of compost fertilizer that can improve the yield and quality of yard-long bean plants. The research was conducted using a Completely Randomized Design (CRD) with 5 compost fertilizer dose treatments: K0 (control), K1 (10 tons/ha), K2 (20 tons/ha), K3 (30 tons/ha), and K4 (40 tons/ha), each replicated 4 times. The observed parameters included plant height, number of leaves, pod length, number of pods per plant, pod weight per plant, and chlorophyll content. The results showed that compost fertilizer application significantly affected all growth and production parameters. Treatment K3 (30 tons/ha) gave the best results with an average plant height of 185.5 cm, 42.3 pods per plant, and pod weight of 245.7 g per plant. The highest chlorophyll content was also obtained in K3 treatment with a value of 48.2 SPAD. Application of compost fertilizer at a dose of 30 tons/ha is the optimal dose for improving the yield and quality of yard-long bean plants, with a production increase of 67.3% compared to the control.